1987
DOI: 10.1002/eji.1830170121
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental zinc (Zn2+) restores antibody formation in cultures of aged spleen cells II. Effects on mediator production

Abstract: In vitro antibody production to T-dependent erythrocyte antigens is depressed as a function of age. Supplementation of antibody-forming cultures with the essential trace element zinc restores the capacity of cells from immunodepressed, aged mice to generate an antibody response. Zn2+ produces maximal enhancement of immune function when it is added to the cultures within the first 24 h. Supernatants obtained from cultures supplemented with zinc from 0-24 h contain soluble, nondialyzable factors which support en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Impairment of 1L-2 production, however, did not block the ability of Zn, applied in vitro, to restore the anti body production of aged spleen cells, although it impaired the ability of aged T cells to proliferate in response to ConA and exogenous 1L-2. The enhancement of antibody produc tion to T-dependent antigens by Zn was mediated by IL-1 and IL-4 [33].…”
Section: Spontaneous Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairment of 1L-2 production, however, did not block the ability of Zn, applied in vitro, to restore the anti body production of aged spleen cells, although it impaired the ability of aged T cells to proliferate in response to ConA and exogenous 1L-2. The enhancement of antibody produc tion to T-dependent antigens by Zn was mediated by IL-1 and IL-4 [33].…”
Section: Spontaneous Proliferationmentioning
confidence: 99%
“…It is known that macrophages with suppressive activities might be induced by in vivo and in vitro application of muramyl dipeptidc (MDP) or lipopolysaccharide (LPS) [28,29], and by nitric oxide (NO)-generating substances [30], Since the inhibitors of prostaglandin (PG)E2 synthesis or o f NO syn thetase [29,30] were able to abrogate the suppressive effect of these macrophages, it was concluded that macrophages are active producers of inhibitory substances, and not sim ply blocked in their stimulating activity. However, the possi bility that PGM-Zn and ZnCI2 have directly inhibited the activity of peritoneal macrophages cannot be excluded, be cause it has been reported that MDP may suppress DNA synthesis in macrophages [31], whereas Zn may decrease the production of 1L-2 in lymphatic cells from aged mice [32,33]. Impairment of 1L-2 production, however, did not block the ability of Zn, applied in vitro, to restore the anti body production of aged spleen cells, although it impaired the ability of aged T cells to proliferate in response to ConA and exogenous 1L-2.…”
Section: Spontaneous Proliferationmentioning
confidence: 99%
“…Zinc, an indispensable metal for normal growth and differentiation, also exerts great influence on certain immune functions through the production, release and action of cytokines (Winchurch et al, 1987;Warner and Lawrence, 1988), and by acting on neutrophils, natural killer cells, lymphocytes and macrophages. The underlying mechanisms through which this element regulates these cells remain unclear (Prasad, 1983;Keen and Gershwin, 1990).…”
mentioning
confidence: 99%
“…Thus, ZIP8-Zn signaling positively controls TCR-induced cytokine production (Figure 5) [144]. In fact, several studies indicate that ZnD suppresses the production of cytokines such as IL-1, IL-2, IL-4, and IFN- γ [93, 145152]. In Th0 and Th1 cell lines cultured in low Zn medium, mitogenic stimulation reduces the mRNA expression of IL-2 and IFN- γ [153].…”
Section: Roles Of Zn and Zn Transporters In The Adaptive Immune Symentioning
confidence: 99%